A revival of effective ploidy: the asymmetry of parental roles in endosperm-based hybridization barriers. (June 2021) - Städler, Thomas; Florez-Rueda, Ana M; Roth, Morgane
Abstract : Interest in understanding hybrid seed failure (HSF) has mushroomed, both in terms of identifying underlying molecular processes and their evolutionary drivers. We review phenotypic and molecular advances with a focus on the 'effective ploidy' concept, witnessing a recent revival after long obscurity. Endosperm misdevelopment has now been shown to underlie HSF in many inter-specific, homoploid crosses. The consistent asymmetries in seed size and developmental trajectories likely reflect parental divergence in key, dosage-sensitive processes. Transcriptomic and epigenomic studies reveal genome-wide, polarized expression perturbations and shifts in parental expression proportions, consistent with small-RNA imbalances between parental roles. Among-species differences in levels of parental conflict over resource allocation enjoy strong support in explaining why differences in effective ploidy may evolve.